Thermally stable high strain and piezoelectric characteristics of (Li, Na, K)(Nb, Sb)O-3-CaZrO3 ceramics for piezo actuators - Lee, Ku-Tak; Lee, Tae-Gon; Kim, Sun-Woo; Chae, Seok-June; Kim, Eun-Ji; Kim, Jeong-Seog; Choi, Ji-Won; Nahm, Sahn (WILEY, 2019)
The 0.97(Na0.5K0.5)(Nb1-xSbx)O-3-0.03CaZrO(3) ceramic with x = 0.09 exhibits a high d(33) of 518 pC/N and a strain of 0.13% at 4.0 kV/mm owing to its orthorhombic-pseudocubic polymorphic phase boundary (PPB) structure. However, these values decreased considerably above 90 degrees C owing to its low Curie temperature (T-C), indicating that its thermal stability is not sufficient for practical applications. Li2O was added to the specimen with x = 0.11 to improve its thermal stability of the strain and d(33) by increasing the T-C without degrading the actual d(33) and strain values. The 0.97(Li0.04Na0.46K0.5)(Nb0.89Sb0.11)O-3-0.03CaZrO(3) ceramic, having an orthorhombic-tetragonal PPB structure, exhibits a d(33) of 502 pC/N and a strain of 0.16%. This large strain was maintained up to 150 degrees C and the d(33) slightly decreased to 475 pC/N at 130 degrees C. Therefore, this lead-free ceramic displays excellent piezoelectric characteristics with improved thermal stability, indicating that it can be applied to piezoelectric actuators.
Keywords: LEAD-FREE PIEZOCERAMICS; PHASE-BOUNDARY STRUCTURES; GIANT PIEZOELECTRICITY; DOMAIN CONFIGURATIONS; TEMPERATURE STABILITY; PERFORMANCE; TRANSITION